Evaluation of Clinical Pro?le of Bipolar and Unipolar Depression Patients- A Clinical Study - Reddy, Musuku Srikanth (Asian Journal of Medical Research, 2020)
Background: The present study was conducted to assess the clinical profile of unipolar and bipolar depressive patients. Subjects & Methods: 74 patients diagnosed with unipolar (40) and bipolar (34) depressive disorders were selected. Depressive cognitions, catatonic features, suicidal thoughts, anhedonia, pseudodementia, dissociative features, panic attacks, delusions, first-rank symptoms, auditory hallucinations, and affective reactivity were recorded. Results: Out of 74 patients, males were 32 and females were 42. Age of onset was 32.2 years in group I and 20.4 years in group II, total duration was 12.4 years in group I and 16.2 years in group II, the number of episodes was 3.4 and 7.1 in group II, the number of hospitalizations was 2.8 in group I and 5.2 in group II, suicidal thoughts were seen in 21 in group I and 24 in group II, anhedonia 10 in group I and 23 in group II, psuedodementia 7 in group I and 13 in group II, dissociative features were seen in 11 in group I and 27 in group II, delusions 4 in group I and 8 in group II, panic symptoms 10 in group I and 18 in group II and auditory hallucination 7 in group I and 18 in group II. The difference was significant (P< 0.05). Conclusion: Authors found that common clinical features were suicidal thoughts, dissociative features, and anhedonia.